Supply chain coordination and firm performance in the construction industry in Gauteng Province - Montso, Mosidi Elizabeth (Vaal University of Technology, 2022)
The construction industry is an important contributor to the economy of South Africa. In this industry, buyers and suppliers work in collaboration with each other to achieve superior supply chain performance. To achieve this, they have to find ways and methods to improve it. The purpose of this study was to investigate supply chain coordination and firm performance in the construction industry in the Gauteng Province. This study considers three drivers: supplier coordination, customer coordination and coordination effectiveness to achieve the performance of the construction industry. In most previous research studies, researchers have overlooked the important considerations and variables of supply chain coordination and firm performances as environmentally-friendly exercises in the construction industry. As a result, there was an abundant necessity to examine how the construction industry should implement a supply chain coordination programme and firm performance as environmentally-friendly practices in the organisational activities to ensure the sustainability of the construction industry. The effective application of SCC and firm performance in the construction industry will benefit all stakeholders. A quantitative approach was adopted in which a survey questionnaire was used to collect data from 414 construction supply chain managers and professional employees in the Gauteng Province. The study used a non-probability convenience sampling technique to select respondents. Data were analysed with the aid of two software packages: the Statistical Package for the Social Sciences (SPSS version 27.0) and the Analysis of Moment Structures (AMOS version 27.0). A confirmatory factor analysis was applied in examining and testing the relationships between observed constructs and their causal latent constructs while structural equation modelling was used to test the hypothesised relationships between constructs. The results revealed that supplier coordination, customer coordination and coordination effectiveness positively and significantly influence firm performance in the construction industry. Further, the study determines that to improve firm performance, the construction industry should advance the stages of trust, guarantee and sustainable relationships with their stakeholders. The results provide useful insights into how the construction industry could benefit from cultivating trust, assurance and sustainable relationships between supply chain partners as well as on how to improve firm performance. Therefore, this study is not only important for construction companies but also for manufacturers, suppliers and customers since most of them will collectively achieve the goal of performing purposeful activities to boost construction performance and sustainability.
M. Tech. (Department of Logistics and Supply Chain Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supplier coordination; Customer coordination; Coordination effectiveness; Firm performance; Dissertations, Academic -- South Africa.; Business logistics.